2015
DOI: 10.1080/02103702.2015.1009232
|View full text |Cite
|
Sign up to set email alerts
|

Resilience and school success of young immigrants / Resiliencia y éxito escolar en jóvenes inmigrantes

Abstract: Secondary school is a high-risk academic period for young immigrants from disadvantaged environments. Despite this, some students are successful in their transition to post-16 education. The present study examines the relationship between resilience and completing school in immigrant young people in Spain. A mixed method design was followed. Ninety-four students in their fourth year of compulsory education participated; they included 19 different nationalities. Results of this study suggest that students who c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
14
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 21 publications
3
14
0
3
Order By: Relevance
“…This idea stems from by Davis, Burnette, Allison and Stone (2010) who observed that a growth mindset was key when students, in a mathematical competition, believed that they were less capable than the rest of their peers. Also, Chen and Pajares (2010) point out that a growth mindset is important when students begin to lower their performance, so future research could analyze whether this intervention would be more effective in students who have seen their Academic performance or with immigrant students since the risk of school failure is higher (Sandín-Esteban and Sánchez-Martí, 2015). Fourth, it should be noted that in this study we used a selection of items from the instrument to evaluate the perception about intelligence, although we provide evidence of reliability and, we Improving the perception of intelligence: a short intervention for Secondary School Students consider that the items adequately represent the construct to be evaluated, it could be that the results with other items were somewhat different.…”
Section: Discussionmentioning
confidence: 99%
“…This idea stems from by Davis, Burnette, Allison and Stone (2010) who observed that a growth mindset was key when students, in a mathematical competition, believed that they were less capable than the rest of their peers. Also, Chen and Pajares (2010) point out that a growth mindset is important when students begin to lower their performance, so future research could analyze whether this intervention would be more effective in students who have seen their Academic performance or with immigrant students since the risk of school failure is higher (Sandín-Esteban and Sánchez-Martí, 2015). Fourth, it should be noted that in this study we used a selection of items from the instrument to evaluate the perception about intelligence, although we provide evidence of reliability and, we Improving the perception of intelligence: a short intervention for Secondary School Students consider that the items adequately represent the construct to be evaluated, it could be that the results with other items were somewhat different.…”
Section: Discussionmentioning
confidence: 99%
“…Being in such a space could have been a motivating factor for the child carers to continue attending school. This finding reinforces the literature that advanced the concept of a special individual having a key role in promoting resiliency among at-risk children in the school setting (Christiansen et al, 1997;Condly, 2006;Cooklin, 2009;Katz, 1997;Sandin-Esteban & Sanchez-Marti, 2015).…”
Section: Teachers Played a Pivotal Role In Keeping Child Carers In Scsupporting
confidence: 86%
“…The study findings confirmed literature which advanced the view that school personnel, including teachers and administrative staff, play a critical role in supporting child carers to continue attending school (Bhana et al, 2006;Christiansen et al, 1997;McMillan & Reed, 1994;Sandin-Esteban & Sanchez-Marti, 2015).…”
Section: Teachers Played a Pivotal Role In Keeping Child Carers In Scsupporting
confidence: 85%
See 2 more Smart Citations